Metasurface-Based Wide-Angle Beam Steering for Optical Trapping - Mengxia He (IEEE Access, 2020)
Metasurfaces become increasingly important for wavefront shaping and beam steering with high efficiency. We propose a wide-angle beam steering device based on all-dielectric metasurfaces consisting of two symmetrical blazed gratings for optical trapping of particles, which can convert the input Gaussian beam to a special beam with intensity gradient along the propagation direction. Two major types of metasurfaces (Pancharatnam-Berry phase and nanoposts) are compared, and dramatic difference is found between them, especially at oblique incidence. We show that the Pancharatnam-Berry phase-based metasurface is more tolerant to the incident angle and that significant optical gradient force can be generated over a large angle range of -50° to 50°, and the maximum attractive force is up to tens of pN/W, with a trapping range of 14 gym for particles of 2.5 μym in diameter. The proposed scheme exhibits great potential to trap a large fraction of particles floating in a microfluidic channel when the beam is dynamically steered.